Speech recognition and utterance verification based on a generalized confidence score. - Myoung-Wan Koo (IEEE Transactions on speech and audio processing)
In this paper, we introduce a generalized confidence score (GCS) function that enables a framework to integrate different confidence scores in speech recognition and utterance verification. A modified decoder based on the GCS is then proposed. The GCS is defined as a combination of various confidence scores obtained by exponential weighting from various confidence information sources, such as likelihood, likelihood ratio, duration, language model probabilities, etc. We also propose the use of a confidence preprocessor to transform raw scores into manageable terms for easy integration. We consider two kinds of hybrid decoders, an ordinary hybrid decoder and an extended hybrid decoder, as implementation examples based on the generalized confidence score. The ordinary hybrid decoder uses a frame-level likelihood ratio in addition to a frame-level likelihood, while a conventional decoder uses only the frame likelihood or likelihood ratio. The extended hybrid decoder uses not only the frame-level likelihood but also multilevel information such as frame-level, phone-level, and word-level confidence scores based on the likelihood ratios. Our experimental evaluation shows that the proposed hybrid decoders give better results than those obtained by the conventional decoders, especially in dealing with ill-formed utterances that contain out-of-vocabulary words and phrases